Dispersed information diffusion with level and schema-based coordination in mobile peer to peer networks - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2007)
Several open ended issues for high resource availability in mobile peer to peer networks have been examined in the recent past. Different approaches were conducted for supporting information distribution and availability, through guided or unguided packet diffusion. The majority of the recently proposed approaches try to benefit from the spatial characteristics of the dynamically varying topologies. In this work a directed information diffusion scheme is examined using a level and schema-based coordination, applied in mobile peer to peer networks. The prioritization degree of any requested advert is modeled and enables directed prioritized diffusions to end mobile users that are traversing a certain geographic region (location based advertisements). The proposed method is robust in disseminating redundant messages to users while maintaining connectivity through Gradual Energy Tree-based (GET) configuration. Simulation is performed for the examination and performance evaluation of the proposed scheme, taking into account the modeled prioritization as well as the diffusion accuracy by using the Hierarchical and Non-hierarchical GET configuration
Keywords: Information diffusion; Level-based coordination; Schema-based coordination; Mobile peer to peer networks; Dispersed dissemination